THE INCIDENT OF STUNTING DAN RISK FACTORS IN CHILDREN - Fadhila, Yoza; Syntia Rahutami; Ali Harokan (Cendekia Medika: Jurnal Stikes Al-Ma`arif Baturaja, 2024)
Stunting is a bad impact of poor nutrition from before birth to early childhood. Stunting cases will cause failure in the growth of children or toddlers, stunted children experience obstacles in the child's cognitive dan motor development. There are still cases of stunting in children, where there are cases of stunting every year, dan there is an increase in cases of stunting. The aim is to find out the factors related to the incidence of stunting dan risk factors in children at the Bigin Teluk Community Health Center, Musi Rawas Regency in 2024. The design of this research is quantitative with a cross-sectional approach.  The population in this study were parents with children seeking treatment at the Bingin Teluk Community Health Center, North Musi Rawas Regency in 2024. The sample for this study was 64 people, the sampling technique was purposive sampling.  This research was carried out on 08 February - 09 March 2024. Data was collected using a questionnaire. Bivariate data analysis used the Chi-Square test dan multivariate logistic regression. The results showed maternal height (p value 0.003), exclusive breastfeeding (p value 0.015) and parity (p value 0.007) education (p value 0.25), antenatal care (p value 1.000), environmental sanitation (p value 0.43) and the role of officers (p value 0.17). The most dominant factor with the incidence of stunting and risk factors in children is exclusive breastfeeding (p value 0.009) (OR 0.22). Conclusion There is a relationship between maternal height, exclusive breastfeeding and parity and the dominant factor in the incidence of stunting is exclusive breastfeeding. For Puskesmas to provide periodic counseling, especially in the MCH program, both at the Puskesmas and at the Posyandu.